2018
DOI: 10.3389/fmicb.2018.00171
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia-Oxidizing Archaea Show More Distinct Biogeographic Distribution Patterns than Ammonia-Oxidizing Bacteria across the Black Soil Zone of Northeast China

Abstract: Black soils (Mollisols) of northeast China are highly productive and agriculturally important for food production. Ammonia-oxidizing microbes play an important role in N cycling in the black soils. However, the information related to the composition and distribution of ammonia-oxidizing microbes in the black soils has not yet been addressed. In this study, we used the amoA gene to quantify the abundance and community composition of ammonia-oxidizing archaea (AOA) and ammonia-oxidizing bacteria (AOB) across the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 76 publications
7
21
0
Order By: Relevance
“…Considering group 1.1b of Thaumarchaeota was taxonomically classified as Nitrososphaera (Bomberg, 2016), the relative abundance of Nitrososphaera (group 1.1b) in this study was comparable to the data observed in our former study of the AOA, in which the Nitrososphaera cluster and the Nitrososphaera sister cluster together comprised 89.34% of the AOA sequences across the same soil samples (Liu et al, 2018). Thus, we hypothesized that the majority of archaea in black soils contribute to nitrification.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Considering group 1.1b of Thaumarchaeota was taxonomically classified as Nitrososphaera (Bomberg, 2016), the relative abundance of Nitrososphaera (group 1.1b) in this study was comparable to the data observed in our former study of the AOA, in which the Nitrososphaera cluster and the Nitrososphaera sister cluster together comprised 89.34% of the AOA sequences across the same soil samples (Liu et al, 2018). Thus, we hypothesized that the majority of archaea in black soils contribute to nitrification.…”
Section: Discussionsupporting
confidence: 87%
“…The copy number of the archaeal genes was calculated by a regression equation to convert the cycle threshold value to the known copy numbers in the standard curves. The copy numbers of the archaeal genes were converted into per gram of dry soil as described in our previous study (Liu et al, 2018). In addition, the ratio of between the archaeal and bacterial 16S rRNA gene copies was also calculated using abundance data of bacterial 16S rRNA genes reported previously (Liu et al, 2016a).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Soil microorganisms from terrestrial habitats are key drivers of critical ecosystem services, such as nutrients cycling (Madsen, 2005 ), soil organic matter (SOM) stabilization and C sequestration (Grandy and Neff, 2008 ; Plaza et al, 2013 ). Although, recent investigations (Xiong et al, 2012 ; Liu et al, 2015 , 2018 ; Xia et al, 2016 ) across different ecosystems have exhibited distinct biogeographic distribution pattern of soil microbes, deeper insights into their distribution and relationship between microbial-mediated nutrient cycling is required to facilitate our understanding of such processes. In recent decades, developments in next-generation high-throughput sequencing have made comprehensive study of soil microbial communities affordable at various scales (Kuang et al, 2013 ; Wu et al, 2013 ; Liu J. et al, 2014 ; Zhang et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%